USE OF THREADS FROM ULTRA-HIGH-MOLECULAR WEIGHT POLYETHYLENE FOR THE PRODUCTION OF REINFORCING FRAMES FOR FIRE PRESSURE HOSES AS ONE OF THE DIRECTIONS FOR IMPROVING THEIR OPERATING CHARACTERISTICS - Myrkhalykov, Zh.U.; Stepanov, S.G.; Kaldybaev, R.T.; Aripbaeva, A.E.; Satayev, M.I. (Scientific Journal of Pedagogy and Economics, 2020)
The problem of choosing the material of synthetic threads for the production of reinforcing cages of fire pressure hoses with improved performance is considered. A promising direction for the production of new durable and high-tech fire pressure hose is proposed. Using along with traditional polyester yarns based on polyethylene terephthalate (PET), ultra-high molecular weight polyethylene (UHMWPE-threads) which, along with carbon and aramid threads belong to the three “superthreads” and differ from traditional threads, it will increase the strength and resistance to abrasion. Such a fire pressure hose will have significantly higher operational characteristics compared to traditional sleeves based on only polyester threads. The resistance of fire pressure hose to abrasion wear will increase several times (due to the use of UHMWPE threads) under the same operating conditions in intensity, the reliability and durability of the fire pressure hose will increase several times, the strength of the fire pressure hose will increase by at least two, and it will meet the requirements of GOST not only on working pressure 1.6 MPa but also 3.0 MPa (at least for sleeves with a diameter of 38 mm, 51 mm, 66 mm, 79 mm) which makes it universal. The use of a complex synthetic threads consisting of a polyester threads and an equally strong UHMWPE threads in the fire pressure hose reinforcing cage will provide significantly higher performance characteristics of the fire pressure hose compared to traditional sleeves based on polyester threads. Despite the rise in price of the fire pressure hose, due to the use of UHMWPE threads, the strength, wear resistance, reliability and durability of the fire pressure hose increase in several times. A patent has been obtained for use in fire pressure hose of weft complex synthetic threads consisting of traditional polyester threads and UHMWPE threads.